2017
DOI: 10.1007/s40506-017-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone Loss in HIV Infection

Abstract: Opinion Statement Human immunodeficiency virus (HIV) infection is an established risk factor for low bone mineral density (BMD) and subsequent fracture, and treatment with combination antiretroviral therapy (cART) leads to additional BMD loss, particularly in the first 1–2 years of therapy. The prevalence of low BMD and fragility fracture is expected to increase as the HIV-infected population ages with successful treatment with cART. Mechanisms of bone loss in the setting of HIV infection are likely multifacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 114 publications
0
29
0
Order By: Relevance
“…Screening was not uniform across sites and was often limited, particularly in public health settings. Additionally, an increasing proportion of patients in the cohort in later years received tenofovir (the median calendar year for patients who initiated zidovudine was 2007 vs. 2010 for those who initiated tenofovir), which has also been associated with osteoporosis risk . The rise in osteoporosis incidence in our cohort most likely reflects introduction of even limited screening and ageing.…”
Section: Discussionmentioning
confidence: 90%
“…Screening was not uniform across sites and was often limited, particularly in public health settings. Additionally, an increasing proportion of patients in the cohort in later years received tenofovir (the median calendar year for patients who initiated zidovudine was 2007 vs. 2010 for those who initiated tenofovir), which has also been associated with osteoporosis risk . The rise in osteoporosis incidence in our cohort most likely reflects introduction of even limited screening and ageing.…”
Section: Discussionmentioning
confidence: 90%
“…Together, these results suggest that low‐grade inflammation promotes or is associated with bone loss in some postmenopausal women. Consistent with these findings, men and women with chronic inflammatory diseases such as rheumatoid arthritis (RA), Crohn's disease, and some viral (ie, human immunodeficiency virus [HIV]) infections develop osteoporosis . Despite these observations, questions as to the nature and the contribution of inflammation to postmenopausal osteoporosis have lingered.…”
Section: Introductionmentioning
confidence: 98%
“…HIV-infected patients are at risk for the development of osteopenia and osteoporosis as a result of many factors, including HIV infection itself, immune suppression, life-long ART, vitamin D deficiency and hypogonadism [3,4,12,26,27,28,38]. To the best of our knowledge, this study is the first investigation of the incidence of osteopenia and osteoporosis to be undertaken in a Bulgarian HIV population.…”
Section: Discussionmentioning
confidence: 98%
“…Data from a number of cross-sectional studies involving both young and elderly HIV-infected patients showed a high incidence of reduced BMD [3,4,16,24,26]. According to one study, osteoporosis is three times more common among HIV-infected patients compared with HIV-negative controls, especially in patients receiving anti-retroviral therapy (ART) [3].…”
Section: Original Articlesmentioning
confidence: 99%
See 1 more Smart Citation